2007
DOI: 10.1016/j.neuropsychologia.2006.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Seeing voices: High-density electrical mapping and source-analysis of the multisensory mismatch negativity evoked during the McGurk illusion

Abstract: Seeing a speaker's facial articulatory gestures powerfully affects speech perception, helping us overcome noisy acoustical environments. One particularly dramatic illustration of visual influences on speech perception is the "McGurk illusion", where dubbing an auditory phoneme onto video of an incongruent articulatory movement can often lead to illusory auditory percepts. This illusion is so strong that even in the absence of any real change in auditory stimulation, it activates the automatic auditory change-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
130
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 60 publications
8
130
2
Order By: Relevance
“…This system seems to be dissociated from auditory spatial processing (27). Nevertheless, our results indicate significant functional connectivity with the transverse temporal gyrus, most likely supporting a bottom-up process underpinning a multisensory component (28). In addition, coactivation, and thus connectivity, in these areas has been correlated with working memory tasks (29).…”
Section: Discussionmentioning
confidence: 57%
“…This system seems to be dissociated from auditory spatial processing (27). Nevertheless, our results indicate significant functional connectivity with the transverse temporal gyrus, most likely supporting a bottom-up process underpinning a multisensory component (28). In addition, coactivation, and thus connectivity, in these areas has been correlated with working memory tasks (29).…”
Section: Discussionmentioning
confidence: 57%
“…ERP studies have revealed that this audiovisual integration occurs during the early stages of perception. The mismatch negativity induced by the illusory phoneme change created by a McGurk effect is not delayed relative to a mismatch negativity recorded after a real auditory change (around 150-250 msec) and the topography of the MMR is similar in both cases (Saint-Amour, De Sanctis, Molholm, Ritter, & Foxe, 2007;Colin et al, 2002). Early cross-modal integration is confirmed by the difference recorded between ERPs to audiovisual speech and the sum of the ERPs to unimodal auditory and visual stimuli on the N1/P2 auditory complex (van Wassenhove, Grant, & Poeppel, 2005).…”
Section: Introductionmentioning
confidence: 73%
“…Here there were extensive structured ERPs and relatively early latency activation to the visual speech stimuli (see also, Saint-Amour et al, 2007). In the present study, a large number of EEG sweeps was collected, increasing the signalto-noise ratios and affording good estimates of the ERPs.…”
Section: Limitations Of the Cdrsmentioning
confidence: 84%